Pyloric and antral strictures following corrosive acid ingestion: A report of four cases - Shukla Ram; Mukhopadhyay Madhumita; Tripathy B; Mandal K; Mukhopadhyay B (Wolters Kluwer Medknow Publications, 2010)
This study reports four children who developed complete stricture of pylorus and antrum of the stomach following accidental ingestion of corrosive agent (toilet cleaner).